Gruel Creep Feeding Accelerates Growth and Alters Intestinal Health of Young Pigs - Timothy E. Boston; Feng Wang; Xi Lin; Suzanne Leonard; Sung Woo Kim; Denny McKilligan; Vivek Fellner; Jack Odle (Animals, 2022)
To combat the stress of weaning, we utilized novel gruel creep feeders to supplement suckling pigs with divergent soluble (n = 6 litters) versus insoluble (n = 6) diets compared with un-supplemented controls (n = 6). Post-weaning, pigs were fed a common phase 1 diet. Average daily weight gains of pigs fed soluble and insoluble creep diets were 53% and 17% greater than control pigs, respectively (p < 0.01). Creep intake was higher (82%) for pigs fed the soluble diet, and the accompanying weight increase was sustained post-weaning (p < 0.02). Villus measures were prematurely altered in soluble-creep-fed pigs (p < 0.01), with decreases in villi length, crypt depth, and villus area pre-weaning. No effects of treatment were detected for VFA concentrations and pH in the cecum. There was an interaction between treatment and age for several pro- and anti-inflammatory cytokines (p < 0.01), where soluble-creep-fed pigs had increased cytokine levels with age, whereas cytokine levels in the insoluble and control groups decreased over time. We conclude that a soluble creep diet fed in a gruel state during the pre-weaning period has a positive impact on weaning weight that is sustained post-weaning, and is accompanied by alterations in the intestinal health of young pigs.